Diabetes and COVID-19 testing, positivity, and mortality: A population-wide study in Northern Italy. (September 2022) - Djuric, Olivera; Ottone, Marta; Vicentini, Massimo; Venturelli, Francesco; Pezzarossi, Annamaria; Manicardi, Valeria; Greci, Marina; Giorgi Rossi, Paolo
Highlights: Type 2 diabetes mellitus (DM2), obesity and cardiovascular diseases (CAVDs) are considered important predictors of COVID-19-related outcomes. However, the role of each of these cardiometabolic factors in COVID-19 death is still unknown. The risk of COVID-19-related death was three times higher among obese vs non-obese patients with DM2. The effect of DM2 and DM2 control on COVID-19-related death is mostly direct, while obesity amplifies it. DM2 duration is an important predictor of COVID-19-related death, and it manifests its effect mostly trough CAVDs. Abstract: AIMS: To assess if patients with type 2 diabetes mellitus (DM2) are: a) at excess risk of undergoing testing, contracting, and dying from SARS-CoV-2 infection compared to the general population; b) whether cardiovascular diseases (CAVDs) contribute to COVID-19-related death; and c) what is the effect of DM2 duration and control on COVID-19-related death. METHODS: This population-based study involved all 449, 440 adult residents of the Reggio Emilia province, Italy. DM2 patients were divided in groups by COVID testing, presence of CAVDs and COVID death. Several mediation analyses were performed. RESULTS: Patients with DM2 had an increased likelihood of being tested (Odds ratio, OR 1.27 95 %CI 1.23–1.30), testing positive (OR 1.21 95 %CI 1.16–1.26) and dying from COVID-19 (OR 1.75 95 %CI 1.54–2.00). COVID-19-related death was almost three times higher among obese vs non-obese patients with DM2 (OR 4.3 vs 1.6, respectively). For COVID-19 death, CAVDs mediated a) just 5.1 % of the total effect of DM2, b) 40 % of the effect of DM2 duration, and c) did not mediate the effect of glycemic control. CONCLUSIONS: For COVID-19-related deaths in DM2 patients, the effect is mostly direct, obesity amplifies it, DM2 control and duration are important predictors, while CAVDs only slightly mediates it.